-7x+5y-6y+8x=

Simple and best practice solution for -7x+5y-6y+8x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+5y-6y+8x= equation:


Simplifying
-7x + 5y + -6y + 8x = 0

Reorder the terms:
-7x + 8x + 5y + -6y = 0

Combine like terms: -7x + 8x = 1x
1x + 5y + -6y = 0

Combine like terms: 5y + -6y = -1y
1x + -1y = 0

Solving
1x + -1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'y' to each side of the equation.
1x + -1y + y = 0 + y

Combine like terms: -1y + y = 0
1x + 0 = 0 + y
1x = 0 + y
Remove the zero:
1x = y

Divide each side by '1'.
x = y

Simplifying
x = y

See similar equations:

| -50x^9/25x^6 | | 3a-(2a-5)=30 | | 3x+3=15+0x | | x^2-3x-15= | | -1-7x=3+2x | | a^3+2=11 | | 48-5x= | | x^3-x^2-x-4=0 | | s^3-s^2-s-4=0 | | 5t^2+9=234 | | 3t+9=t+13 | | 1+3(2x-7)=8-4(3x+1) | | 5(4+m)-3(3m-1)=-9 | | 3a+10=3a-4 | | 9ab^2+27a^3-27a^2b-b^3+c^3=0 | | 2z+6=36 | | 5p+9=4p+8 | | -2(6z-3)+13(z-7)=-81-9 | | 25x=4x^(1/3) | | 9s-8(s-10)+3=84 | | 3x+8y=59 | | -3(s-2)+4s=-11-2 | | 7(s-2)+4s=-11-2 | | 5(3x+8)+5x=5(2d+10)-36 | | 4(4b+6)=3(2b-18) | | y=150-s | | 4(3y-1)-2y=56 | | 3(2n-6)=4m-10 | | 9(m-1/3)=9 | | 13=145-11q | | 20=90-5q | | (y+2)-2(y+3)=4(x+1) |

Equations solver categories